2005
DOI: 10.1016/j.jtcvs.2004.12.028
|View full text |Cite
|
Sign up to set email alerts
|

Phosphodiesterase type 4 inhibitor rolipram inhibits activation of monocytes during extracorporeal circulation

Abstract: Rolipram inhibited changes in adhesion molecule expression and interleukin-6 release by activated monocytes in simulated extracorporeal circulation. This study suggests that phosphodiesterase type 4 inhibition could be feasible therapeutic strategy to prevent exaggerated inflammatory response and organ injury in patients undergoing cardiopulmonary bypass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…In recent investigations, it has been accepted that membrane‐anchored rTFs are quite similar to the natural TF . Our previous studies have demonstrated that simulated CPB activates platelets, neutrophils, and monocytes, and promotes the formation of microaggregates within 30 minutes after starting simulated CPB . Moreover, platelet activation is known to be initiated rapidly after starting CPB.…”
Section: Discussionmentioning
confidence: 98%
“…In recent investigations, it has been accepted that membrane‐anchored rTFs are quite similar to the natural TF . Our previous studies have demonstrated that simulated CPB activates platelets, neutrophils, and monocytes, and promotes the formation of microaggregates within 30 minutes after starting simulated CPB . Moreover, platelet activation is known to be initiated rapidly after starting CPB.…”
Section: Discussionmentioning
confidence: 98%
“…Monocytes were in direct contact with a synthetic surface during the experimental procedure but were not specifically treated or activated; nonetheless, this extracorporeal contact resulted in monocytes activation 28, 29. Using microfluidic methods, the extracorporeal human monocytes strongly adhered to autologous ICAM-1 and to mouse ICAM-1 even without additional treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The attraction of monocytes to activated platelets is hypothesized to be through the secretion of the monocyte chemoattractant protein-1 (MCP-1) which has been recently shown to be markedly induced by activated platelets [62]. The monocyte-platelet interaction activates the monocyte into a proinflammatory state and upregulation of the surface integrin, CD11b mediates the firm adhesion to platelets [12,63]. Our results show a significant increase in monocyte CD11b upon exposure to ECC and NO released from the polymer-coated ECC reduced this enhanced CD11b expression.…”
Section: Discussionmentioning
confidence: 99%